A review of foot-and-mouth disease in Ethiopia: epidemiological aspects, economic implications, and control strategies - Girma Zewdie; Mirtneh Akalu; Wondwossen Tolossa; Hassen Belay; Getaw Deresse; Mariamawit Zekarias; Yeneneh Tesfaye (Virology Journal, 2023)
Abstract Foot-and-mouth disease (FMD) is a contagious viral disease that affects the livelihoods and productivity of livestock farmers in endemic regions. It can infect various domestic and wild animals with cloven hooves and is caused by a virus belonging to the genus Aphthovirus and family Picornaviridae, which has seven different serotypes: A, O, C, SAT1, SAT2, SAT3, and Asia-1. This paper aims to provide a comprehensive overview of the molecular epidemiology, economic impact, diagnosis, and control measures of FMD in Ethiopia in comparison with the global situation. The genetic and antigenic diversity of FMD viruses requires a thorough understanding for developing and applying effective control strategies in endemic areas. FMD has direct and indirect economic consequences on animal production. In Ethiopia, FMD outbreaks have led to millions of USD losses due to the restriction or rejection of livestock products in the international market. Therefore, in endemic areas, disease control depends on vaccinations to prevent animals from developing clinical disease. However, in Ethiopia, due to the presence of diverse antigenic serotypes of FMD viruses, regular and extensive molecular investigation of new field isolates is necessary to perform vaccine-matching studies to evaluate the protective potential of the vaccine strain in the country.